Grouping of unified indices in the optimization of cost readjustments of road works in Peru - Layza Mendiola, Ricardo Martin; Alzamora de los Godos Urcia, Luis Alex; Calderón Saldaña, Jully Pahola; Sotil Chávez, Andrés; Sánchez Carlessi, Hector Hugo; Valladolid Marcos, Fiorella Sthefany; Pineda Medina, Javier Alejandro (LACCEI, 2024)
The study aims to determine the preliminary grouping of Unified Indices to improve price readjustments using the polynomial formulas of road works in Peru year 2021. The methods established by Supreme Decree No. 011-79-VC were used, as well as compared with an optimization proposal related to monthly readjustments, work deductions and variation of offers. They were applied in 3 national road works where the parameters of executed readjustments were extracted. The results showed that there is a very strong correlation between these four parameters and the adjustments made. The Optimal grouping variable has a strong moderate correlation for the three (03) works under study (0.74, 0.996, 0.905). It is concluded that the optimal grouping of Unified Indices for price readjustments is based on the consideration of monthly readjustments, applying the respective deductions, in addition to the variation of offers for the execution of road works.